2013
DOI: 10.7852/ijie.2013.26.1.041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Daphniamagna for the Ecotoxicity Assessment of Alkali Leachate from Concrete

Abstract: The cladoceran Daphniamagna has been used as an aquatic test species in aquatic toxicology. To evaluate the aquatic toxicity of leachate from concrete, the immobilization of D. magna was observed after treatment of various concentrations of leachate specimens. Reliabilities of the culture condition and the experimental protocol for acute toxicity test were successfully achieved from the standard toxicity test. The leachates were prepared from the mixture of Ordinary Portland Cement (OPC) and pozzolanic admixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…This is because eluates from RA (A1) with a pH value of 12.5 were found much less toxic to the crustacean than the A2 and A3 eluates with pH values equal to 12.4 and 12.1, respectively (Table 8). Therefore, other factors, for instance the release of chemical compounds, including metals, from these materials into water due to leaching, may be influencing the biological response of the test-organism to the eluates' samples, as reported by others [13,19].…”
Section: Ecotoxicological Characterization (Ec) Of Ra Fa A1 A2 Andmentioning
confidence: 88%
See 2 more Smart Citations
“…This is because eluates from RA (A1) with a pH value of 12.5 were found much less toxic to the crustacean than the A2 and A3 eluates with pH values equal to 12.4 and 12.1, respectively (Table 8). Therefore, other factors, for instance the release of chemical compounds, including metals, from these materials into water due to leaching, may be influencing the biological response of the test-organism to the eluates' samples, as reported by others [13,19].…”
Section: Ecotoxicological Characterization (Ec) Of Ra Fa A1 A2 Andmentioning
confidence: 88%
“…Choi et al [13] proved Daphnia magna could be suitable to evaluate the ecotoxicity of leachate from concrete. The leachates of cement samples in acute toxicity test showed 100% Daphnia magna immobilization upon 24 h exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [ 38 ] these leachates were classified as inhibitory—mild toxic ( Table 5 ). The ecotoxicity of concrete leachates can result both from toxic compounds presence and alkalinity [ 12 , 39 , 40 ]. Besides the high conductivity in RA 2 and particularly RA 3 ( Table 4 ) the pH values remained highly alkaline even after dilution of the original leachates unlike in the case of NA, RA 1, and RA 4 samples.…”
Section: Resultsmentioning
confidence: 99%
“…The most sensitive bioindicator of ecotoxicity was daphnia which was already recommended for ecotoxicological assessment of concrete leachates [ 39 , 42 ]. Our study also confirmed duckweed as a suitable plant test organism because of its sensitivity where toxic effect can be detected on both morphological and biochemical level and various symptoms such as necrosis can be observed.…”
Section: Resultsmentioning
confidence: 99%